Cytotoxicity of Cultured Canine Primary Hepatocytes Exposed to Itraconazole Is Decreased by Pre-treatment With Glutathione - Kirk, Natalie M.; Vieson, Miranda D.; Selting, Kim A.; Reinhart, Jennifer M. (Frontiers in Veterinary Science, 2021)
Objective: To identify the effect of glutathione (GSH) on cell survival in a novel in vitro model of itraconazole (ITZ)-associated hepatotoxicity using canine primary hepatocytes. Sample: Commercially sourced, cryopreserved male dog (Beagle) primary hepatocytes from a single donor. Procedures: Using a sandwich culture technique, canine primary hepatocytes were exposed to serial dilutions of ITZ. Calcein AM, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), and neutral red were investigated as potential cell viability assays. Hepatocytes were then pre-incubated with GSH, exposed to serial dilutions of ITZ, and cell viability determined at 4 and 24 hours post-ITZ exposure. Each condition was performed in technical triplicate and the effect of time, GSH concentration, and ITZ concentration on % cytotoxicity assessed using a multivariate linear regression model. Tukey’s post hoc test was used to detect individual differences. Results: The neutral red cell cytotoxicity assay was chosen based on its superior ability to detect dose-dependent changes in viability. Hepatocyte cytotoxicity significantly increased with ITZ concentration (P < 0.001) and time (P = 0.004) and significantly decreased with GSH treatment (P < 0.001). Conclusions and clinical relevance: This in vitro model demonstrates dose- and time-dependent ITZ-induced cytotoxicity, which is similar to clinical changes observed in canine patients and in in vivo rodent studies. Pre-treating with GSH is protective against in vitro cell death. These results suggest that GSH precursors may have a role in the management or prevention of ITZ-associated hepatotoxicity in dogs. Clinical trials are needed to evaluate their utility for this adverse drug reaction.